(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Previous measurement studies have shown the existence of path exploration and slow convergence in the global Internet routing system, and a number of protocol enhancements have been proposed to remedy the problem. However, existing measurements were conducted only over a small number of testing prefixes. There has been no systematic study to quantify the pervasiveness of Border Gateway Protocol (BGP) slow convergence in the operational Internet, nor any known effort to deploy any of the proposed solutions. In this paper, to present the measurement results that identify BGP slow convergence events across the entire global routing table. The data shows that the severity of path exploration and slow convergence varies depending on where prefixes are originated and where the observations are made in the Internet routing hierarchy. In general, routers in tier-1 Internet service providers (ISPs) observe less path exploration, hence they experience shorter convergence delays than routers in edge ASs; prefixes originated from tier-1 ISPs also experience less path exploration than our data show that the convergence time of route fail- over events is similar to that of new route announcements and is significantly shorter than that of route failures. This observation is contrary to the widely held view from previous experiments but confirms the earlier analytical results. The effort also led to the development of a path-preference inference method based on the path usage time, which can be used by future studies of BGP dynamics.